Impending Danger: The Meaning of Danger as a Legal Requirement for Involuntary Psychiatric Treatment in the Norwegian Criminal Justice System - Mindestrømmen, Martin (Bergen Journal of Criminal Law & Criminal Justice, 2019)
A proposal for the revision of the rule regulating involuntary psychiatric treatment of criminally insane offenders has been accepted by the Norwegian parliament. As a result, greater emphasis will be placed on the requirement of ‘danger’ in future decisions on whether criminally insane offenders shall be subjected to sanctions. This paper gives an overview of the rule in question and makes a preliminary analysis of the legal contents of the danger requirement. Possible problem-areas that have not been addressed in the proposal for revision are identified. The need for future research is explained.